A fotografia amadora no México: Club Fotográfico de México e a presença da folclorização na construção da identidade nacional mexicana - 1950 - Grecco, Priscila Miraz De Freitas [UNESP] (Universidade do Estado de Santa Catarina, 2016)
In this study we reflect about the Photographic Club of Mexico an institution focused on amateur photography in Mexico City in the early years of its operation in late 1950. We understand the fotoclube as a route to be operated by the history of photography from the moment that present themselves as places of social arrangements in which various issues involving the practice and theorization of photographic image can be observed ranging from photographic propaganda image status of the country. In this sense, Mexico Photographic Club played a central role in building an image foclorizada of the country and its popular culture, its landscape, thereby contributing to the consolidation of an identity governing model, primarily through its guidelines for creation of the photographic image, leading the amateur photographer from choosing the theme to be addressed, through the technical and aesthetic that could be used to photograph the country, its landscape, its culture, its people.
The amateur photography in Mexico: For a plural history of photography
Keywords: Amateur photography; Mexicanidad; Photography - clubs; Photography - Mexico